OPTIMIZATION OF LIBRARY SERVICES TO INCREASE LIBRARY INTEREST IN READING - Amelia, Nisa; Ananda, Refisa (PERSPEKTIF: Journal of Social and Library Science, 2024)
Nowadays, library services are very diverse compared to some of the past. Information Technology gives new meaning to the services provided by libraries. There are several libraries that support and expect library users to be satisfied with the services provided by librarians. The background of this research is to see how the Optimization of Library Services to Increase Reading Interest in Library Users in the Padang Panjang City Library, optimizing this service is carried out by carrying out activities that can attract the attention of the visitors to reading interest. Not only that, librarians must also be able to discuss how to allow visitors to visit the library of the City of Padang Panjang. This research is a qualitative research with descriptive type. Data collection is done by means of observation, interviews, and documentation studies conducted using analytical techniques developed by Miles and Huberman. The results of this study indicate that researchers found several ways to optimize library services to increase interest in reading (1) library management that is more professional, (2) library development with adequate facilities, (3) increase activities to attract reading interest..